2001
DOI: 10.1897/1551-5028(2001)020<0706:astemt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Tenax® Extraction Method to Determine the Availability of Sediment-Sorbed Organic Compounds

Abstract: A simple method to determine the availability of sediment-sorbed organic contaminants was developed and validated. For 10 polycyclic aromatic hydrocarbons, 4 polychlorinated biphenyls, and 9 chlorobenzenes in 6 sediments, we measured the fraction extracted by Tenax in 6 and 30 h. These fractions were compared with the rapidly desorbing fractions determined by consecutive Tenax extraction. Extraction by Tenax for 30 h completely removed the rapidly desorbing fraction plus some part of the slowly desorbing fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…3,22,23,31,[48][49][50] The amounts of HOCs desorbed are dependent on the exposure time of the sorbent to the sediment slurry, correlations between F rap and desorption fraction at the single time-point were observed. 51 As a result, Cornelissen et al 51 suggested that a simplified Tenax extraction at a single time-point, representative of F rap , could also be correlated to organism tissue residues.…”
Section: Tenax Extraction Theoretical Considerations and Methodologiesmentioning
confidence: 99%
“…3,22,23,31,[48][49][50] The amounts of HOCs desorbed are dependent on the exposure time of the sorbent to the sediment slurry, correlations between F rap and desorption fraction at the single time-point were observed. 51 As a result, Cornelissen et al 51 suggested that a simplified Tenax extraction at a single time-point, representative of F rap , could also be correlated to organism tissue residues.…”
Section: Tenax Extraction Theoretical Considerations and Methodologiesmentioning
confidence: 99%
“…The first hypothesis would have 466 to be verified by implementing a cell culture similar to the one realised by Tiehm (1994) to 467 assess whether PAHs-degraders could use saponins from Quillaja saponaria bark as primary 468 nutrients over PAHs and the second by evaluating the bioavailability of PAHs in the presence of 469 saponins through the use of Tenax® beads for example [Cornelissen et al, 2001]. 470…”
Section: Chrysenementioning
confidence: 99%
“…There are new, sophisticated approaches that can characterize the bioavailability of contaminants and they may construct lines of evidence between contamination and e¡ects on organisms living in the sediment [8,73]. These are at ¢rst simple resin extraction methods (e.g., use of Tenax) to determine the availability of sediment-sorbed organic compounds [74].…”
Section: Surveillance Investigations (''Memory E¡ect'')mentioning
confidence: 99%